Satisfying Students’ Psychological Needs During the COVID-19 Outbreak in German Higher Education Institutions - Teuber, Ziwen; Jia, Hao; Niewöhner, Thomas (Frontiers in Education, 2021)
The COVID-19 outbreak has been a worldwide challenge for the higher education community. Under lockdown measures, meeting students’ needs and encouraging their engagement in academic work have never been more urgent and challenging. In this study, we investigated the relationship between students’ satisfaction with institutional strategies, students’ optimism and pessimism, satisfaction with basic psychological needs, engagement in academic work, intention to drop out from studies, depression, and well-being. We conducted an online self-report study on N = 477 German college and university students (77.25% females, mean age = 23.96 years, SD = 4.78). The results of structural equation models showed that students’ satisfaction with institutional strategies was positively related to their basic psychological need satisfaction and engagement. Students’ optimism was positively associated with need satisfaction and engagement, whereas pessimism was negatively associated with them. Furthermore, students’ academic engagement was negatively linked to dropout intentions, whereas psychological need satisfaction was linked to ill- and well-being. The findings of this study suggest that acknowledging students timely about the institutional strategies of examinations and courses and supporting students to engage in academic activities are important institutional tasks during the crisis.